2018
DOI: 10.1093/ptj/pzy098
|View full text |Cite
|
Sign up to set email alerts
|

Structural Validity of the Short Musculoskeletal Function Assessment in Patients With Injuries

Abstract: In a broad range of patients with injuries, the SMFA-NL may be best scored and interpreted using a 4-factor structure. Other factor structures showed insufficient structural validity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…[4][5][6][7][8][9] The two indices were originally reported to be valid, reliable and responsive, 10,11 although recently the Function and Bother indices were shown to have insufficient structural validity in Dutch trauma patients using the SMFA-NL. 12 The findings indicated that the two indices are not a valid representation of the latent construct physical functioning. Only a four-subscale configuration consisting of the subscales Upper Extremity Dysfunction, Lower Extremity Dysfunction, Problems with Daily Activities and Mental and Emotional Problems demonstrated sufficient structural validity.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…[4][5][6][7][8][9] The two indices were originally reported to be valid, reliable and responsive, 10,11 although recently the Function and Bother indices were shown to have insufficient structural validity in Dutch trauma patients using the SMFA-NL. 12 The findings indicated that the two indices are not a valid representation of the latent construct physical functioning. Only a four-subscale configuration consisting of the subscales Upper Extremity Dysfunction, Lower Extremity Dysfunction, Problems with Daily Activities and Mental and Emotional Problems demonstrated sufficient structural validity.…”
Section: Introductionmentioning
confidence: 94%
“…Only a four-subscale configuration consisting of the subscales Upper Extremity Dysfunction, Lower Extremity Dysfunction, Problems with Daily Activities and Mental and Emotional Problems demonstrated sufficient structural validity. 12 Although the four-subscale structure showed sufficient structural validity in a broad range of trauma patients, additional clinimetric properties (reliability, construct validity and responsiveness ) have not yet been evaluated. Evaluation of these properties is required to justify usage in clinical and research settings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SMFA contains 46 items that are scored on a five-point Likert scale. The Dutch SMFA-NL consists of four subscales: Upper Extremity Dysfunction, Lower Extremity Dysfunction, Problems with Daily Activities and Mental and Emotional Problems [ 13 , 14 ]. Scores range from 0 to 100.…”
Section: Methodsmentioning
confidence: 99%
“…Patients received the standard SMFA-NL. The SMFA-NL uses the same items as the original American SMFA, but uses a different factor structure [ 14 ] . The clinimetric properties of the SMFA-NL have been shown to be sufficient in patients with traumatic injuries [ 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%